Adequacy of Inclusion of Older Adults in NIH‐Funded Phase III Clinical Trials - Lockett, Jaron; Sauma, Samir; Radziszewska, Barbara; Bernard, Marie A. (Journal of the American Geriatrics Society (JAGS), 2019)
In the United States, the population aged 65 and older is rapidly growing, and this group uses more healthcare resources and has unique healthcare needs that do not exist in younger populations. However, it was reported that older adults are excluded or underrepresented in clinical trials for several diseases. We examined phase III clinical trials funded by the National Institutes of Health found in www.clinicaltrials.gov from 1965 to 2015 that addressed top causes for hospitalization and/or disability‐adjusted life years in older adults: congestive heart failure (n = 45), cardiac dysrhythmias (n = 24), coronary atherosclerosis (n = 106), heart attack (n = 76), stroke (n = 113), chronic obstructive pulmonary disease (n = 14), pneumonia (n = 48), lung cancer (n = 117), prostate cancer (n = 65), and osteoarthritis (n = 15). We then analyzed the representation of older adults in these studies. We found that 33% of studies had arbitrary upper age limits, and 67% of studies reported mean and/or median ages that skewed younger than expected for the disease or condition of interest. Beyond explicit exclusion by age, older adults were often implicitly excluded based on various comorbid conditions such as polypharmacy/concomitant medication (37%) or cardiac issues (30%). We conclude that outcomes of these trials may not be fully generalizable to the general population of older adults. J Am Geriatr Soc 67:218–222, 2019. See related Editorial by George Kuchel in this issue.